Animated Video Based on Contextual Approach on Fraction Arithmetic Operations Material for Grade V Elementary School - Ayu Renata Fridalina Rusanti; I Wayan Wiarta; Dewi Anzelina (Undiksha Press, 2025)
The problem addressed in this study is the lack of instructional media that can enhance students' interest and understanding of fraction operations through an approach that is relevant to everyday life. The aim of this study is to develop contextual-based animated video media for teaching mathematics, specifically the topic of fraction operations, in fifth-grade elementary school. This research employs the ADDIE development model, with data collected through questionnaires, objective tests (multiple-choice), and analyzed using descriptive quantitative and inferential statistical techniques. The research subjects included one media expert, one subject matter expert, one instructional design expert, and fifth-grade elementary school students consisting of three students for individual trials and nine students for small group trials. The results showed that the animated video media design in digital format covered competencies, content, example problems, and developer profiles, with an expert validation score of 92.5% (categorized as excellent). The product feasibility tests indicated that the animated video media is suitable for use, with validation results from subject matter experts (92%), instructional design experts (95%), media experts (94%), individual trials (92.5%), and small group trials (93.05%), all categorized as excellent. The effectiveness test using a t-test analysis showed that the students’ post-test average score (91.87) exceeded the BSKAP standard score (86), with the t-test result showing t-count = 3.73 > t-table = 1.75 at a 5% significance level (α = 0.05). Therefore, it can be concluded that the contextual-based animated video media is appropriate and effective for use in teaching fraction operations in fifth-grade elementary school.